Meteor Men : expanded edition - Parker, Jeff, 1966- (Oni Press, 2022)
"One summer night, Alden Baylor sits in a field watching the largest meteor shower in human history. What begins as teenage adventure becomes something more--the celestial event brings travelers who will change the world completely, and Alden discovers a connection to one of them. How does a young man who had to grow up fast handle the invasion of his planet? Can Alden keep humanity from oblivion?"--Page 4 of cover.